Analysis of Commercial Law Studies, Its Influence on Inflation in A Country's Economy, and Legal Politics on The Phenomenon of Counterfeit Money Printing and Circulation in Indonesia - Nomensen Freddy Siahaan; Agustina Wati; Ine Ventyrina (Journal of Social Research, 2025)
The police dismantled a syndicate of counterfeit money making and circulation operating in the UIN Alauddin Makassar Library building. The police have identified 17 suspects with evidence worth hundreds of trillions of rupiah. This case began when one of the perpetrators paid motorcycle installments at one of the leasing companies on Jalan Pelita Lamengi, Bontoala Village, Pallangga District, Gowa Regency. The police who received the report intervened and finally uncovered this syndicate. This study employs normative legal research methods, which focus on analyzing legal norms and regulations relevant to the research topic. Normative legal research is a scientific procedure to discover the truth through logical reasoning based on the established principles of law. This method systematically examines legal materials, including legislation, case law, and legal doctrines, to provide a comprehensive understanding of the issue under study. The data used in this study are primarily secondary in nature, consisting of laws, regulations, legal precedents, and scholarly legal commentaries that are pertinent to the topic of Commercial Law dan Political Law. Once the relevant legal materials were collected, the data analysis process began with systematically interpreting legal texts, focusing on their application to sexual violence and commercial law. This included evaluating the purpose, scope, and application of laws and identifying any inconsistencies or gaps. A comparative legal analysis was also employed, where necessary, to contrast Indonesian laws with international conventions and legal practices from other countries, highlighting differences and suggesting improvements. Finally, the findings were synthesized to propose recommendations for enhancing legal protections against sexual violence and human trafficking. This detailed methodological approach ensures that the research is grounded in thorough legal analysis, enabling readers to understand the steps taken to collect and interpret the data without needing to refer to external sources. The author concludes that the meaning of a cause that is not prohibited or halal in the context of the agreement is related to the agreement's content or the goals to be achieved by the parties involved. The content of an agreement must not be contrary to law, morality, or public order. This is in accordance with the provisions of Article 1337 of the Civil Code, which explains that a cause is prohibited if the cause is prohibited by law or if the cause is contrary to morality or public order. This is where the problem occurs. The object of the counterfeit money trade turned out to violate the provisions of laws and regulations. Basically, the prohibition related to counterfeit money has been expressly regulated in Articles 26 and 27 of Law Number 7 of 2011 concerning Currency as follows: Article 26 jo. Article 36 Everyone is prohibited from counterfeiting rupiah, with a maximum penalty of imprisonment of 10 years and a maximum fine of Rp10 billion. If it is associated between political and legal purposes with the case of printing and circulation of counterfeit money, these activities cannot provide welfare to the community because if the circulation of counterfeit money is high and the public does not know that the money is fake, it can interfere with the inflation of the Rupiah currency because there is too much money circulating in the community and it is getting out of control. If this continues, it will have an impact on the country's economic sector and can create an economic crisis in a country.